2018
DOI: 10.2147/jpr.s154462
|View full text |Cite
|
Sign up to set email alerts
|

Current pain management strategies for patients with erythromelalgia: a critical review

Abstract: Erythromelalgia (EM) is a rare disorder characterized by erythematous, warm, painful extremities, which is often precipitated by cold conditions. The pathophysiology of EM is incompletely understood. Recent investigations have identified sodium channelopathy as a genetic cause for this pain condition, classified as primary inherited EM. Other subtypes are idiopathic EM and secondary EM. The management of pain in EM is challenging as no single therapy has been found to be effective. There is varying response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 97 publications
2
29
0
3
Order By: Relevance
“…This confirms the observations of Friborg et al that suggest that erythromelalgia is not an isolated disease but that it is a pattern of response of cutaneous microvasculature [4]. Tham and Giles rapported that erythromelalgia is associated with a neuropathy of small fibers and primary vasculopathies, characterized by an intermittent increase of blood flow, hypoxia, and possibly shunts, with increase in local cellular metabolism [5]. Due to the hypothesis of shunts, substances that alter the distribution of skin blood flow can improve the cutaneous oxygenation and induce symptoms relief [6].…”
Section: Sirsupporting
confidence: 88%
“…This confirms the observations of Friborg et al that suggest that erythromelalgia is not an isolated disease but that it is a pattern of response of cutaneous microvasculature [4]. Tham and Giles rapported that erythromelalgia is associated with a neuropathy of small fibers and primary vasculopathies, characterized by an intermittent increase of blood flow, hypoxia, and possibly shunts, with increase in local cellular metabolism [5]. Due to the hypothesis of shunts, substances that alter the distribution of skin blood flow can improve the cutaneous oxygenation and induce symptoms relief [6].…”
Section: Sirsupporting
confidence: 88%
“…The 5-HT and histamine antagonist cyproheptadine and pizotifen effectively relieved the burning pain and increased skin temperature [ 56 , 57 ]. A survey of the members of The Erythromelalgia Association reported marked improvement in 40% of patients with antihistamines, including desloratadine, chlorpheniramine, and diphenhydramine [ 58 ]. A child with erythromelalgia responded to cetirizine, and his symptoms aggravated once cetirizine was discontinued [ 59 ].…”
Section: Clinical Applications In Dermatologic Diseasesmentioning
confidence: 99%
“…Patients typically resort to foot lifting, cooling feet by fans or immersing them in water or iced water to reduce or relief pain. Although immersion in cold water is effective for mild cases, it can result in ulceration and maceration of foot skin leading to infection [19,116]. Recently, it has been reported that behavioural therapy reduced dependence on water immersion in PEM patients [67].…”
Section: Primary Erythromelalgiamentioning
confidence: 99%
“…There is no consensus on pharmacotherapy. Among effective drugs are non-selective sodium blockers (lignocaine, mexiletine and carbamazepine) [ 82 , 116 ] which have been shown to inhibit Na V 1.7 [ 120 , 133 ].…”
Section: Primary Erythromelalgiamentioning
confidence: 99%